Representasi Citra Perempuan dalam Cerita Rakyat Dayak Kenyah Tilo Enggau - Jogarni Maria Marta; Nina Queena Hadi Putri (JENTERA: Jurnal Kajian Sastra, 2025)
This study aims to reveal the image of women in the Tilo Enggau folktale from the Dayak Kenyah community as a symbolic, spiritual and socio-cultural discourse. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews with informants from the Dayak Kenyah community and documentation of unpublished folklore texts as objects of study. The data were analyzed using three feminist perspectives: radical feminism, cultural feminism and ecofeminism. The results of the study show that the female characters in the story appear as independent figures who reject the norms of marriage, experience supernatural pregnancies and give birth to descendants from heaven. The female characters in this story not only carry out biological functions, but also represent strong socio-cultural constructions. Women are the center of lineage and have symbolic authority as guardians of social harmony. This representation is emphasized through the sacred ancestral speech "ayen nei kini ni, ameq su yaq alaq tilo enggau labok ni" which means "don't come here because we are the grandchildren of the one who took tilo enggau fell," as a symbol of women's authority over lineage and communal harmony. Abstrak Penelitian ini bertujuan untuk mengungkap citra perempuan dalam cerita rakyat Tilo Enggau dari masyarakat Dayak Kenyah sebagai wacana simbolik, spiritual dan sosial budaya. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara mendalam terhadap narasumber dari komunitas Dayak Kenyah serta dokumentasi teks cerita rakyat yang belum pernah dipublikasikan sebagai objek kajian. Data dianalisis menggunakan tiga perspektif feminisme: feminisme radikal, feminisme kultural dan ekofeminisme. Hasil penelitian menunjukkan bahwa tokoh perempuan dalam cerita tampil sebagai figur mandiri yang menolak norma pernikahan, mengalami kehamilan supranatural dan melahirkan keturunan dari kayangan. Tokoh perempuan dalam cerita ini tidak hanya menjalankan fungsi biologis, tetapi juga merepresentasikan konstruksi sosial-budaya yang kuat. Perempuan menjadi pusat garis keturunan dan memiliki otoritas simbolik sebagai penjaga harmoni masyarakat. Representasi ini ditegaskan melalui tuturan sakral leluhur “ayen nei kini ni, ameq su yaq alaq tilo enggau labok ni” yang berarti "jangan datang ke sini karena kami adalah cucu dari yang mengambil tilo enggau jatuh,” sebagai simbol otoritas perempuan atas garis keturunan dan harmoni komunal.